Forward-stimulated Brillouin scattering in silicon-core fibers - Yao, Yao; Wang, Tao; Liu, Yi; Wang, Bingjie; Zhang, Mingjiang (Frontiers in Physics, 2023)
As a new type of semiconductor fiber, silicon-core fiber has a higher nonlinear effect compared with silica fiber. Forward-stimulated Brillouin scattering (FSBS) as a typical optical nonlinear effect holds strong promise for applications in, for example, fibre optic sensing. The study of the FSBS effect in silica-core fibres facilitates further theoretical exploitation of the potential of FSBS in fibre optic sensing. In this paper, the FSBS in silicon-core fiber is studied by finite element method. The model is based on a silicon-core fiber, whose silicon core diameter is 4and silica cladding diameter is 33.4 , and the optical field modes are classified by vector method to obtain the acoustic field modes excited by FSBS —-radial mode R0m and torsional radial mode TR2m. The FSBS gain of the fiber shows that R0m has the best coupling with TM and TE optical modes, and TR2m has the best coupling with HE optical modes. It is concluded that the sound field frequency shift of R0m is more sensitive to the change of the effective refractive index of the optical field than that of TR2m. The factors affecting the gain are refined into photoelastic effect (PE) and moving boundary perturbations (MB), and their contributions to the total gain are summarized. Finally, it is confirmed that a similar strong FSBS gain of 365.57 (1/mw) can be obtained for a silicon-core fiber without reducing the size to the usual size of a silicon waveguide.